CITARUM HARUM: COMPARISON STUDY OF EXISTENCE OF MILITARY AND LOCAL GOVERNMENT POWER IN THE REVITALIZATION OF THE CITARUM RIVER BASIN IN KARAWANG REGENCY - Prastio, Luki Oka; Indriyany, Ika Arinia; Widodo, Widodo (Journal of Social Politics and Governance (JSPG), 2024)
This research is motivated by the increasing popularity of military involvement in various government programs, especially the Indonesian Army. One of them is the Citarum Harum Program. Implementing the Citarum Harum Program involves multiple sectors, including the Indonesian Army, Regional Government, industry, and society. In Karawang Regency, the military's involvement in the Citarum Harum program has received great trust from various stakeholders. It is even believed to bring success if the local government does so. The purpose of this study is to reveal how the existence of military and government strength in revitalizing the Citarum River. This study uses several aspects of collaborative governance from Ansell and Gash (2007). The study results show that the Indonesian Army is more prevalent in implementing the Citarum Harum Program than the Karawang Regency local government. Measured based on aspects of military strength and resources, it is superior to the local government. In addition, the existence of sanctions and incentives for collaborating with the military is rigid towards the success of tasks compared to local governments. The ability to mediate and facilitate the military is superior due to regulatory support and complete trust from industry and society.